Digital Literacy in Teaching English for Young Learners: A Critical Research Review - Wachidaturrohmah; Afifi, Nur (EduLine: Journal of Education and Learning Innovation, 2025)
This study explored various studies related to digital literacy in teaching English to young learners in Asia. A systematic review was conducted using the PRISMA methodology to analyze studies published between 2014 to 2024. The screening process found seven relevant studies selected to be reviewed. The data were synthesized to explore the importance and challenges of digital literacy in English language teaching for young learners. The results revealed that using digital tools like digital storytelling, digital pictures, and video-based instruction enhances students’ engagement and students’ skills. However, unequal access to technology and teachers limited digital literacy were identified as challenges. The findings pointed the need of training programs for teachers to enhance digital literacy skills. Policymakers and schools should collaborate to provide the technology and make sure the internet can be accessed equally. Overall, this study highlighted that in teaching English, the use of technology and traditional method should be balance.